A link between β-catenin and hypertrophy: evaluation and meta-analysis - Palchevska, O.L.; Macewicz, L.L.; Piven, O.O. (Вiopolymers and Cell, 2016)
Heart is a terminally differentiated organ almost unable to regenerate. The remodeling and hypertrophic growth are believed to be the main mechanisms of heart renovation after workloads or injury. Although there have been major advances in the identification of the genes and signaling pathways involved in mediating hypertrophy, further characterization of the underlying molecular mechanisms is needed due to the overall complexity of this process. Aim. The present work is an attempt to systematically assess the previous research on a β-catenin role in the heart muscle hypertrophy development. We hypothesized that β-catenin is a member of universal and conserved regulatory pathway for different tissues and species. To test this hypothesis, we performed the meta-analysis of experimental data available in different databases. Methods. The literature data were analyzed via Origin 8.0 using the simple regression and two-way ANOVA methods. Results. The results allowed selecting the most reproducible hypertrophy markers which were appropriate for the study of β-catenin function in the hypertrophy response (SERCA, actin DIF, Axin-2, c-myc, CD1, BNP, ANP and total protein/DNA index). The analysis shows that a decrease in the β-catenin expression has an ambiguous effect on heart hypertrophy. Conclusion. We have drawn interesting conclusions on the model and species-specific link between the β-catenin level and hypertrophy development, as well as between some hypertrophic markers and β-catenin expression on one hand, and hypertrophy development etc. on the other hand. The results also allowed selecting the most reproducible hypertrophy markers. Серце – прийнято вважати термінально диференційованих органом, який майже не регенерує. Перебудови міокарда і гіпертрофічний зростання є основними механізмами відновлення функції серця після надмірних навантажень і пошкоджень. В останні десятиліття багато робіт було присвячено ідентифікації генів і сигнально-регуляторних шляхів, залучених до вишеозначенние процесыв, але через складність останніх дослідження молекулярних механізмів, що лежать в основі розвитку гіпертрофії, не втрачає своєї актуальності. Мета . Дана робота є спробою систематично оцінити у вигляді мета-аналізу сучасні дослідженя, які стосуються ролі білка β-катеніна в розвитку гіпертрофії міокарда. Методи . Літературні дані, проаналізовано Origin 8.0 за допомогою методів простої регресії і two-way ANOVA. Результати . Відібрано маркери (SERCA, actin DIF, Axin-2, c-myc, CD1, BNP, ANP, а також індекс співвідношення вмісту білка і ДНК), що відтворюються в різних експериментальних умовах, які можуть бути використані для дослідження ролі β-катеніна в формуванні гипертрофического відповіді міокарда. Показано, що зниження рівня експресії β-катеніна має неоднозначний ефект на розвиток гіпертрофії міокарда. Висновки . Результати аналізу дозволяють зробити висновки про вплив експериментальної моделі на результати дослідження рівня експресії β-катеніна і його внесок в розвиток гіпертрофії, а також на існування такого зв'язку між деякими гіпертрофічна маркерами і рівнем експресії β-катеніна з одного боку і розвитком гіпертрофії – з іншого. Також встановлено, які з гипертрофических маркерів є найбільш відтвореними при різних умовах розвитку гіпертрофії. Сердце – принято считать терминально дифференцированным органом, который почти не регенерирует. Перестройки миокарда и гипертрофический рост являются основными механизмами восстановления функции сердца после чрезмерных напряжений и повреждений. В последние десятилетия много работ было посвящено идентификации генов и сигнально-регуляторных путей, вовлеченных в вышеобозначенные процессы, но из-за сложности последних исследование молекулярных механизмов, лежащих в основе развития гипертрофии, не теряет своей актуальности. Цель. Данная робота является попыткой систематически оценить в виде мета-анализа исследований, доступных в современной литературе, которые относятся к установлению роли белка β-катенина в развитии гипертрофии миокарда. Методы. Литературные данные, были проанализированы Origin 8.0 с помощью методов простой регрессии и two-way ANOVA. Результаты. Отобраны маркеры (SERCA, actin DIF, Axin-2, c-myc, CD1, BNP, ANP, а также индекс соотношения содержания белка и ДНК), воспроизводимые в разных экспериментальных условиях, которые могут быть использованы для исследования роли β-катенина в формировании гипертрофического ответа миокарда. Показано, что снижение уровня экспрессии β-катенина имеет неоднозначный эффект на развитие гипертрофии миокарда. Выводы. Результаты анализа позволяют сделать выводы о влиянии экспериментальной модели на результаты исследования уровня экспрессии β-катенина и его вкладе в развитие гипертрофии, а также на существование такой связи между некоторыми гипертрофическими маркерами и уровнем экспрессии β-катенина с одной стороны и развитием гипертрофии – с другой. Также установлено, какие из гипертрофических маркеров являются наиболее воспроизводимыми при разных условиях развития гипертрофии.